Improve Understanding of English by Using Music for Elementary School Students - Yunanti, Windha (Prosiding University Research Colloquium, 2021)
The purpose of this article is to discuss about how to improve students’ understanding of English using music. The method used in data collection is a journal review. Various media and methods can be used to improve students’ understanding of English and one of them is music. Music is one of the media that is useful for developing children’s understanding of the English language. Different types of music can be used. By using music students can easily understand and understand English.